Digital pedagogies and biotechnical realities: Education and life after the COVID-19 pandemic - Brailas, Alexios (Homo Virtualis, 2020)
What would have taken years to change in the world we knew, took just a few months during a global pandemic. Millions of teachers, therapists, and other practitioners around the world whose work requires direct contact with people, dived into every synchronous and asynchronous platform they could find. They had to in order to continue their work with students or clients, to maintain connections, to empower people during the crisis, to ensure that nobody felt alone, to protect and strengthen life, and to resist a vicious invisible threat. All these practitioners struggled to ensure physical distancing did not result in social or emotional distancing, and managed to do so through web technologies and digital media. The social pattern of life, the very pattern that allowed coronavirus to threaten humanity, is the same pattern helped maintain life during lockdown by taking advantage of digital media.